Evaluasi Sosialisasi Pencegahan Penggunaan Narkoba di Wilayah Jakarta: Studi pada Kelompok SLTP dan SLTA - Victor Pudjiadi; Jemmi Y.Kaseger (Jurnal Syntax Admiration, 2024)
Drug use by adolescents in Jakarta is an urgent public health problem. Many outreach programs have been created to stop drug abuse in schools. However, it is still unclear whether these programs are effective, especially in terms of how they can change students' knowledge, views, and behaviors. The focus of this study is students of Junior High School (SLTP) and Senior High School (SLTA) in Jakarta to evaluate how effective the socialization program for drug use prevention is. This research uses a qualitative approach, which involves in-depth interviews and focused group discussions. Data were collected from 20 students, 10 teachers, and 5 facilitators of socialization programs in high schools (SLTP) and high schools in Jakarta. The thematic analysis method is used to analyze the data to find patterns, themes, and perceptions related to program effectiveness. As a result of the socialization program, students understand the dangers of drugs better. Changes in attitudes and behaviors, however, are not always clearly visible. Most students stated an increase in their awareness. However, there is uncertainty about how this knowledge can be applied. The absence of parental support, irrelevant materials, and time constraints are some of the problems found by teachers and facilitators in running the program. The results of the drug prevention socialization program in Jakarta have succeeded in improving students' understanding, but it is difficult to consistently change attitudes and behaviors. Recommendations for improvement include increased parent participation, better socialization materials, and program adjustments to meet student needs.